The Efforts to Foster Students’ Skill in Making Questions through Thinking Tool (Question Matrix) Development (Jurnal Pendidikan IPA Indonesia, 2019)
Asking questions and making statements is not easy for students. Many researchers have developed a question pattern, but it has several weaknesses. The question pattern generally has not guided the students to ask low to high level of questions; also, they have no idea what the issue is about and how to naturally propose the question. This research aimed to develop a thinking tool named Question Matrix. This thinking tool intends to train students’ questioning skills in various question levels based on learning purposes. This research was divided into two; small and large scale. The small scale was performed in the even semester, academic year of 2015/2016 while the large scale was in the even semester, academic year of 2016/2017. The method referred to the 4D (Define, Design, Develop, and Disseminate) model. The sample consisted of 104 students. The data were collected through students’ worksheets to collect students’ questions and questionnaires to collect the data of students’ responses to the use of the question matrix. The data collection was conducted in 8 meetings. The quality of students’ questions was scored by using the question quality assessment rubric and categorized according to the revised Bloom taxonomy to determine the percentage of LOT and HOT questions. The research results indicated that Question Matrix had helped the students in making questions. Before the use of Question Matrix, the average small scale research result was 48% (LOT) and 52% (HOT) and increased by 32.50% (LOT) and 67.502% (HOT) after the tool application. In the large scale research, the average cognitive level was 35% (LOT) and 73.5% (HOT). Also, 45.8% of the questions belonged to the ‘Good’ category. In sum, the findings indicated that the Question Matrix is sufficient to be used as guidance in making questions.